Vertical Trabeculae are Thinned More Than Horizontal Trabeculae in Skeletal-Unloaded Rats. - Vegger, Jens; Brüel, Annemarie; Thomsen, Jesper; Vegger, Jens Bay; Brüel, Annemarie; Thomsen, Jesper Skovhus (Calcified Tissue International, 2015)
Skeletal unloading results in a rapid thinning of the trabecular bone network, but it is unknown whether vertical and horizontal trabeculae are equally affected. Therefore, the purpose of the present study was to investigate whether horizontal and vertical trabeculae were thinned similarly during skeletal unloading in rats. Fifty-seven 16-week-old female Wistar rats were randomized into six groups: baseline; control 4 weeks; botulinum toxin A (BTX) 4 weeks; control 8 weeks; BTX 8 weeks; and two BTX injections 8 weeks (BTX + BTX8). The BTX animals were injected in the right hind limb with 4 IU BTX at the start of the study, while the BTX + BTX8 were also injected with 2 IU BTX after 4 weeks. The animals were killed after 0, 4, or 8 weeks. The distal femoral metaphyses were μCT scanned, and the strengths of the femoral necks, mid-diaphyses, and distal femoral metaphyses were ascertained. Disuse resulted in a significant loss of BV/TV, thinning of the trabeculae, and decrease in the degree of anisotropy, and in a significant reduced bone strength after both 4 and 8 weeks. The ratio of horizontal to vertical trabecular thickness (Tb.Th.horz/Tb.Th.vert) and the ratio of horizontal to vertical bone volume (BV.horz/BV.vert) were significantly higher in BTX animals than in control animals. In addition, the horizontal and vertical trabecular thickness probability density functions were more similar in BTX animals than in control animals. In conclusion, skeletal unloading decreased BV/TV, Tb.Th, the degree of anisotropy, and mechanical strength, while BV.horz/BV.vert and Tb.Th.horz/Tb.Th.vert were increased. This indicates that the more loaded vertical trabeculae are pronouncedly more thinned than the less loaded supporting horizontal trabeculae during unloading.